Achieving ‘appeal’ through Kansei approach - Teddy Marius Soikun; Ag. Asri Ag. Ibrahim (Penerbit UMS, 2019)
The design of animation character design depends on the principle of ‘Appeal.’ However, to define this important principle is difficult as it is a perplexing principle as it is based on personal opinion. To ‘achieve’ and understand ‘appeal’ need a systematic way, and this project proposes ‘Kansei Engineering’ approach. The project adopts Kansei Engineering method to achieve ‘appeal’ by selecting a popular animation domain and use qualitative method to analyze the appeal factor through the adaptation of Kansei Words in which, this project renamed to Viewer’s Impression Word (VIW). Through VIW, the project managed to identify ‘appeal’ factors through multivariate analysis such as factor analysis, Partial Least Squares and PCA, it managed to propose systematic loose principles. The loose principle is called Animation Character Design Appeal Principles (ACDAP) that may assist animators and designers in understanding and achieving ‘appeal’ in their designs.